Influences of Catecholamine Contents on Tetrahydrobiopterin Metabolism - Kuzuya Hiroshi; Sakamoto Hideo; Fujita Ko (Pteridines, 1998)
The influence of changes in catecholamine metabolism on tetrahydrobiopterin biosynthesis was investigated in cultured rat pheochromocytoma PC12 cells. The increase in the cellular dopamine content after treatment with the MAO-COMT inhibitor or dopamine produced decreases in the GTP-cy-clohydrolase I (GTPCH-I) activity and total biopterin content. On the contrary, the catecholamine increase after treatment with nerve growth factor produced increases in the GTPCH -I activity and total biopterin content. On the other hand, the decrease in the dopamine content after tyrosine hydroxylase (TH) inhibitor treatment produced decreases in the GTPCH-I activity and total biopterin content, but the catecholamine decrease (the DOPA content increased about 3.4-fold) after aromatic L-amino acid decarboxylase inhibitor treatment produced a decrease in the GTPCH-I activity. These results suggest that an increase in dopamine content that is not directly related to the action of TH plays a role in down-regulation of tetrahydrobiopterin biosynthesis and that when the changes in catecholamine metabolism are strongly associated with the action of TH, tetrahydrobiopterin biosynthesis is regulated depending on the necessity for TH.